The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2015
DOI: 10.1111/ced.12718
|View full text |Cite
|
Sign up to set email alerts
|

Are there sufficient numbers of low-risk basal cell carcinomas to justify general practitioners (family physicians) carrying out basal cell carcinoma surgery?

Abstract: Low-risk BCCs suitable for excision by GP surgeons are of low prevalence and it would be difficult for GPs to maintain competencies in BCC surgery. Dermatologists should continue to provide the lead in skin cancer diagnosis, treatment and management.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
7
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 9 publications
0
7
0
Order By: Relevance
“…Trends in ageing populations means that supply of appropriate treatment such as excisional surgery may be stretched in State healthcare systems such as the UK National Health Service, and it has been estimated that the number of cases presenting to dermatologists will increase by 50% by 2030 (Madan et al, 2010). Such a trend has resulted in guidance for more family practitioners to provide treatment for low risk lesions in the community (Fremlin et al, 2016). Although excisional surgery remains the gold standard for most common types of BCC, a range of non-surgical approaches are available including photodynamic therapy (Wang et al, 2015), topical imiquimod cream, topical 5-fluorouracil, and topical ingenol (Clark et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Trends in ageing populations means that supply of appropriate treatment such as excisional surgery may be stretched in State healthcare systems such as the UK National Health Service, and it has been estimated that the number of cases presenting to dermatologists will increase by 50% by 2030 (Madan et al, 2010). Such a trend has resulted in guidance for more family practitioners to provide treatment for low risk lesions in the community (Fremlin et al, 2016). Although excisional surgery remains the gold standard for most common types of BCC, a range of non-surgical approaches are available including photodynamic therapy (Wang et al, 2015), topical imiquimod cream, topical 5-fluorouracil, and topical ingenol (Clark et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Despite high and rising incidence rates of BCCs reported in the literature, 27 41 we found that only a small proportion of BCCs can be considered ‘low-risk’ when taking into account body site, diameter and histological subtype, 41–43 which was recently confirmed by Fremlin et al . 42 Aside from the low volume, the number of excisions performed by GPs in the intervention group was even lower. According to the GPs this may have been partly related to the training being insufficient to change GPs’ practices.…”
Section: Discussionmentioning
confidence: 95%
“…Only 37% of model 2 GPs took written consent. In a review of 1743 BCCs excised over a 32-month period by GPs, 6 only 3% were considered to be ‘low risk’ according to NICE 2010 criteria. The authors concluded that low-risk BCCs are of low prevalence, which therefore leads to difficulties for GPs to maintain competencies.…”
Section: Introductionmentioning
confidence: 99%